Anterior Opening-Wedge Proximal Tibial Osteotomy for Slope Correction of Genu Recurvatum - Jack Dirnberger BS; Morgan D. Homan DO; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: Symptomatic genu recurvatum is defined as greater than 5° of knee hyperextension and can be caused by osseous deformity, soft tissue laxity, or a combination. Common symptoms include pain, weakness, instability, decreased range of motion, leg length discrepancy, and stretching of the posterior capsuloligamentous structures of the knee. In instances where the genu recurvatum is caused by reverse tibial slope, literature supports the use of anterior opening-wedge proximal tibial osteotomy (OW PTO) to treat genu recurvatum by increasing tibial slope. Correction of anterior slope to a more anatomic, posterior orientation allows any stressed ligaments to return to their normal tension and restores the native biomechanics of the knee. Indications: The primary indication for OW PTO is genu recurvatum that is nonresponsive to physical therapy or genu recurvatum with concurrent ligamentous injury. The heel-height test provides an objective assessment for the identification and measurement of knee hyperextension. Technique Description: 2 guide pins are placed parallel to the tibial plateau, engaging the posterior cortex. A small micro sagittal saw is used to cut the anterior cortex. Osteotomes are used to complete the osteotomy, preserving a posterior hinge. An opening spreader device is placed and opened slowly while keeping the posterior cortex intact. The new slope is maintained by use of an opening wedge osteotomy plate and screws. Allograft bone graft is packed thoroughly into the osteotomy site. Fluoroscopy is used throughout the case to assess appropriate orientation and depth of the osteotomy, as well as the final opening width. Results: A review of 5 studies demonstrated adequate reduction in hyperextension, with a mean knee hyperextension ranging from 17° to 32° preoperatively and 0° to 7° postoperatively. Patients had significantly improved postoperative clinical outcomes compared with the preoperative state. Discussion/Conclusion: Anterior OW PTO has been shown to be a safe method of accurately correcting tibial plateau slope for the treatment of genu recurvatum. Patients can expect correction of knee hyperextension, restoration of anatomic posterior tibial slope, decreased posterior tibial translation, and increased subjective outcome scores. Patient Consent Disclosure Statement: The author(s) attest that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.